Find the number of ordered triples ( p , q , r ) of primes such that p q = r + 1 and 2 ( p 2 + q 2 ) = r 2 + 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
your answer is not valid for 2nd equation
I think your answer doesn't work:
You say ( p , q , r ) = ( 2 , 3 , 5 ) is a solution. Now, the problem say that the following equation must be true:
2 p 2 + q 2 = r 2 + 1
Substituting your answer we get:
( 2 ∗ ( 2 2 ) ) + ( 3 2 ) = ( 3 2 ) + 1
8 + 9 = 9 + 1
Which is clearly wrong.
Log in to reply
You put 2 p 2 + q 2 instead of 2 ( p 2 + q 2 ) . Also, you substituted r = 3 not r =5. Have another check and you should find that (2,3,5) and (3,2,5) are in fact valid
As you said r cant be even... thus p q is indeed even...and therefore either p or q is 2, nevertheless notice that if p = 2 then the second equation doesnt follow since the LHS is odd while the RHS is even. This means that q = 2 . So we get a system of equations: 2 p = r + 1 ; 2 p 2 + 4 = r 2 + 1 Which has no integer solutions. So there are no order triples of primes that satisfy the equation.
(-2,-3,5) also solution from both equation.
Log in to reply
Definition of primes have to be positive
Same soln i also had...
Thought only of (2,3,5) not (3,2,5).....
Problem Loading...
Note Loading...
Set Loading...
Given p q = r + 1
r must be an odd prime because if r is even, then r = 2 and r + 1 = 3 ⇒ r = 3 which not possible since p , q are primes. Hence r is odd.
This means that p q is even and hence one of p , q must be 2 .
Suppose p is 2 . This means that 2 q = r + 1
Squaring both sides
4 q 2 = r 2 + 1 + 2 r ⇒ 4 q 2 = 2 ( p 2 + q 2 ) + 2 r ⇒ 2 q 2 = 2 p 2 + 2 r ⇒ 2 q 2 = 8 + 2 r ⇒ q 2 = 4 + r ⇒ q 2 − 4 = r ⇒ ( q + 2 ) ( q − 2 ) = r
Since r is a prime, one of ( q + 2 ) , ( q − 2 ) must be equal to one. If q + 2 = 1 ⇒ q = − 1 which is not possible. Hence q − 2 = 1 ⇒ q = 3 ⇒ r = 5
Hence we find the solution ( p , q , r ) = ( 2 , 3 , 5 ) . Similarly taking q = 2 we can get ( p , q , r ) = ( 3 , 2 , 5 ) .
Hence there are two solutions.